2021
DOI: 10.2196/26843
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Kidney Graft Survival Using Machine Learning Methods: Prediction Model Development and Feature Significance Analysis Study

Abstract: Background Kidney transplantation is the optimal treatment for patients with end-stage renal disease. Short- and long-term kidney graft survival is influenced by a number of donor and recipient factors. Predicting the success of kidney transplantation is important for optimizing kidney allocation. Objective The aim of this study was to predict the risk of kidney graft failure across three temporal cohorts (within 1 year, within 5 years, and after 5 year… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The research extends to the prediction of graft survival approach by proposing a new three-phase approach, that is, (i) data processing phase, (ii) feature selection phase, and (iii) prediction phase [ 23 ].…”
Section: Proposed Ab-ann Methodologymentioning
confidence: 99%
“…The research extends to the prediction of graft survival approach by proposing a new three-phase approach, that is, (i) data processing phase, (ii) feature selection phase, and (iii) prediction phase [ 23 ].…”
Section: Proposed Ab-ann Methodologymentioning
confidence: 99%
“…Various related work showed that AI approaches based on medical input data can result in accurate and robust statistical models to predict patient outcomes [30][31][32][33][34]. For example, supervised tree-based ML algorithms, for example, RF and Extreme Gradient Boosting, have shown promising results for classification tasks for posttransplant risks, for example, for graft failure, patient survival, or graft loss within a certain time period [35][36][37][38][39][40]. However, most of the existing approaches were research-driven and had only limited access to real-world medical data for their work, for example, using the Scientific Registry of Transplant Recipients data set [41].…”
Section: Using ML For Cpmsmentioning
confidence: 99%
“…Thus, existing risk communication tools such as [10] identify survival functions obtained from the Cox PH model at these time points. Many previous publications follow this classification approach [3, 11, 12]. However, this approach requires to train a model for each time point.…”
Section: Introductionmentioning
confidence: 99%